1986
DOI: 10.1093/oxfordjournals.eurheartj.a061979
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous coronary artery dissection: Case report and evidence for a defect in collagen metabolism

Abstract: Spontaneous coronary artery dissection is a rare disease with a higher prevalence in women, especially in the post-partum state. In one case, we attempted to relate this pathology to a disorder in collagen metabolism. A 32-year-old woman presented two episodes of myocardial infarction, 2 and 4 months after delivery which were shown to be due to two consecutive coronary artery dissections on coronary angiogram. Collagen metabolism was investigated in skin fibroblast cultures derived from the patient, and in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
5

Year Published

1994
1994
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(40 citation statements)
references
References 0 publications
0
35
0
5
Order By: Relevance
“…It has been noted to mostly affect multiparous women over the age of thirty 13 and commonly involves the left main and left anterior descending arteries 14 . The exact mechanism for this is unknown; however, it is thought that the increased level of progesterone results in structural changes of the vessel walls making them more susceptible to spontaneous dissection [15][16] . With the increased hemodynamic stress of pregnancy and delivery, small tears in the intima of these compromised vessels can occur leading to the dramatic clinical picture that occurs 16 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted to mostly affect multiparous women over the age of thirty 13 and commonly involves the left main and left anterior descending arteries 14 . The exact mechanism for this is unknown; however, it is thought that the increased level of progesterone results in structural changes of the vessel walls making them more susceptible to spontaneous dissection [15][16] . With the increased hemodynamic stress of pregnancy and delivery, small tears in the intima of these compromised vessels can occur leading to the dramatic clinical picture that occurs 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Bonnet at al. [5] suggest that low collagen synthesis as in patients with Elhers-Danlos syndrome type IV or III might be responsible for an alteration in the coronary vessel walls, resulting in spontaneous coronary dissection these diseases are known to be due to an inborn defect in collagen metabolism. On the other hand, since an intimal tear was found only infrequently at autopsy, disruption of vasa vasorum leading to intramedial hemorrhage and subsequent dissection without intimal tear has been proposed as a possible mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in connective tissue that occur during pregnancy are probably caused by the high estrogen level, 4 but SCAD also occurs in men, leading to the necessity of formulating a multifactorial theory of pathogenesis. 5 Angitis has been implicated in the pathogenesis and Kearney et al 6 reported autopsy cases with eosinophilic infiltration of the adventitia of the involved coronary artery.…”
Section: Discussionmentioning
confidence: 99%